Systemic Corruption and Mismanagement in Azerbaijan's Water Sector: The Human and Economic Toll - Gubad Ibadoghlu (SSRN, 2024)
The pervasive reach of corruption extends far beyond individuals, impacting entire populations and critical infrastructure. This paper examines a tragic event that occurred on October 22, 2024 in Baku's Sabunchu district, where two drivers lost their lives, not to floodwaters, but to the consequences of systemic corruption embedded in the city's sewer infrastructure. Their deaths illustrate the tangible and fatal outcomes of financial mismanagement and the inefficiency in the allocation of public funds. This study delves into the corruption surrounding the allocation of resources to “Azersu” (Azerwater) OJSC, prior to the establishment of the Azerbaijan State Water Resources Agency. Furthermore, it analyzes the role of international financial aid, particularly from the World Bank, alongside revenue from water consumers, to expose the extent of mismanagement within Baku's water resources. The findings highlight the broader societal impact of these governance failures, emphasizing the urgent need for reform.
Keywords: 330; Azerbaijan; Corruption; Mismanagement; Water Sector; Water Supply; Sanitation Services